Rough Decision Making of Facial Expression Detection - Praba, B.; Charumathi, P.; Anand, Bhavana (Communications in Mathematics and Applications, 2024)
This paper introduces a novel framework named rough decision making which extends the principles of rough set theory. The mathematical model proposed consists of a fuzzy intervalvalued knowledge-based information system that includes a non-empty finite universe of objects, a derived interval-valued fuzzy set of attributes, and a fuzzy interval-valued set of decisions. To manage complexity, the roughness of decision-making is introduced by defining lower and upper rough decisions for each object. Further, this model is implemented on a real-time affective image database RAF-DB for facial expression detection. This approach is found to provide a comprehensive analysis of facial expressions, demonstrating effective classification even in the presence of uncertainty.
Keywords: Rough set theory; Decision making problems; Facial expression detection